2017
DOI: 10.3390/su9040528
|View full text |Cite
|
Sign up to set email alerts
|

Tailor-Made Feedback to Reduce Residential Electricity Consumption: The Effect of Information on Household Lifestyle in Japan

Abstract: Abstract:Residential smart metering and energy feedback have attracted worldwide attention toward reducing energy consumption and building a sustainable society. Many theoretical studies have suggested the importance of personalized information; however, few feedback demonstrations have focused on household lifestyle. This paper presents a pilot program of energy feedback reports based on analytical methods to show the relationship between electricity consumption and household lifestyle in Japan. One type of r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…(Schultz et al 2007, Allcott 2011, Ayres et al 2013, Costa and Kahn 2013, Carroll et al 2014, Ozawa et al 2017, Sudarshan 2017. Some interventions avoided the issue of the 'boomerang effect' (where low energy users realize that their peers are less efficient and begin increasing consumption) by making a comparison to an efficient neighbour of similar characteristics, rather than an average neighbour (Ayres et al 2013, Asensio and Delmas 2015).…”
mentioning
confidence: 99%
“…(Schultz et al 2007, Allcott 2011, Ayres et al 2013, Costa and Kahn 2013, Carroll et al 2014, Ozawa et al 2017, Sudarshan 2017. Some interventions avoided the issue of the 'boomerang effect' (where low energy users realize that their peers are less efficient and begin increasing consumption) by making a comparison to an efficient neighbour of similar characteristics, rather than an average neighbour (Ayres et al 2013, Asensio and Delmas 2015).…”
mentioning
confidence: 99%
“…Providing real-time feedback to households on their energy use is an incentive to reduce energy consumption (Ruokamo et al, 2022). Most of the information feedback is currently done through smart grid tools, or other monitoring tools (Kendel et al, 2017;Ozawa et al, 2017;Lazowski et al, 2018) combined with regression analysis, found the impact of energy feedback reports on household lifestyles, and contributed to a reduction in household electricity consumption. The economic incentives and government financial subsidy policies for reducing energy consumption, can motivate households to adopt energy efficiency measures and increase welfare (Vuelvas and Ruiz, 2017;Zhang G et al, 2021).…”
Section: Enhancing Energy-saving Intentionsmentioning
confidence: 99%